Medicine in ancient Assur a microhistorical study of the Neo-Assyrian healer Kiṣir-Aššur - Arbøll, Troels P. (Leiden Boston Brill, 2020)
Acknowledgements -- List of Figures and Tables -- Abbreviations and Symbols -- Symbols and Further Abbreviations -- Introduction -- 1.1 Colophons -- 1.2 Mesopotamian Medicine -- 1.3 Authorship -- 1.4 Proof and Possibility -- 1.5 Scope and Structure -- Framework and Background -- 2.1 Microhistory -- 2.2 Framework -- 2.3 Background for Studying Kiṣir-Aššur -- 2.4 Quantifying and Contextualizing Kiṣir-Aššur's Texts -- Kiṣir-Aššur's Magico-Medical Education as šamallû ṣeḫru -- 3.1 Complex Diagnoses in Kiṣir-Aššur's šamallû ṣeḫru Texts -- 3.2 Principles Understood Through Examples -- 3.3 The Head: BAM 9 -- 3.4 The "Strings" and "Inner" Body -- 3.5 Snakes, Scorpions and Horses: A Discussion of RA 15 pl. 76 -- 3.6 Gaining an Understanding of Anatomy and Physiology -- 3.7 Preparation for Other Duties as šamallû ṣeḫru -- 3.8 Summary -- Training in Anatomy and Physiology as šamallû ṣeḫru -- 4.1 The Role of Venom in Kiṣir-Aššur's Anatomical Understanding -- 4.2 Veterinarian Knowledge in Kiṣir-Aššur's Education -- 4.3 Excursus: Animal Variants of Human Illnesses -- 4.4 Animal and Human Physiology: The Reverse of RA 15 pl. 76 -- 4.5 Summary -- Further Apprenticeship: šamallû to mašmaššu ṣeḫru -- 5.2 The šamallû mašmaššu ṣeḫru-phase -- 5.3 The mašmaššu ṣeḫru-phase -- 5.4 Excursus: The ša Nabû tuklassu-phrase -- 5.5 Summary -- Kiṣir-Aššur's mašmaššu-phase -- 6.1 Texts with Colophons Including the Title mašmaššu -- 6.2 Making House Calls: Discussion of KAR 230 -- 6.3 Ritually Protecting the Houses of Clients: Discussion of KAR 298 -- 6.4 Namburbi-rituals and House Calls: KAL 4 no. 7 and LKA 115 -- 6.5 Other Technical Literature: CT 37 pl. 24f. -- 6.6 Summary -- Additional Texts that May Belong to the mašmaššu-phase -- 7.1 Omission and Inclusion of Titles -- 7.2 Tablets Without Kiṣir-Aššur's Professional Title -- 7.3 Tablets with Broken Colophons -- 7.4 The mašmaššu-phase and Purpose Statements -- 7.5 A Discussion of the Dated Tablet KAR 267 -- 7.6 Other Technical Literature: BAM 307 and ACh Supp. 2 24 -- 7.7 Summary -- Kiṣir-Aššur's mašmaš bīt Aššur-phase -- 8.1 The Title mašmaš bīt Aššur -- 8.2 Medical Texts from Kiṣir-Aššur's mašmaš bīt Aššur-phase -- 8.3 Tested Prescriptions Among the Medical Texts -- 8.4 Panaceas Among the Medical Texts -- 8.5 Ritual Texts from Kiṣir-Aššur's mašmaš bīt Aššur-phase -- 8.6 Texts Connected to the Aššur Temple -- 8.7 Summary -- Situating Kiṣir-Aššur's Knowledge Production -- 9.1 Kiṣir-Aššur's Overall Medical Focus -- 9.2 Numbered Nisḫu-extracts -- 9.3 Catch-lines and Duplicate Passages in Kiṣir-Aššur's Texts in Relation to the Therapeutic Series Ugu -- 9.4 The Exorcist's Manual (EM) -- 9.5 Kiṣir-Aššur and the Scholarly Traditions in Assur -- 9.6 Summary -- Synthesis and Conclusion -- Catalogue of Texts -- Edition of RA 15 pl. 76 -- Transliteration -- General Observations -- Commentary -- Bibliography 346 -- Index.
In Medicine in Ancient Assur Troels Pank Arbøll offers a microhistorical study of a single exorcist named Kiṣir-Aššur who practiced medical and magical healing in the ancient city of Assur (modern northern Iraq) in the 7th century BCE. The book provides the first detailed analysis of a healer's education and practice in ancient Mesopotamia based on at least 73 texts assigned to specific stages of his career. By drawing on a microhistorical framework, the study aims at significantly improving our understanding of the functional aspects of texts in their specialist environment. Furthermore, the work situates Kiṣir-Aššur as one of the earliest healers in world history for whom we have such details pertaining to his career originating from his own time
Includes bibliographical references and index
Keywords: Medicine, Assyro-Babylonian; Medicine, Ancient